P26 Measuring the value of a consultant-led Community Respiratory (CORE) Multidisciplinary Team (MDT) in a deprived inner city area: Achieving parity in respiratory care for housebound sick patients. (12th November 2015) - Heightman, M; Dullaghan, D; Rafferty, A; Jones, E; Townes, H; Gardiner, L; Dzingai, J; Nimoh-Bing, C; Broomfield, H; Fabris, G; Dharmagunawardena, R; Restrick, L; et al.
Abstract : Introduction: The shift of chronic respiratory disease management to the community has stimulated development of multidisciplinary community respiratory services (CORE-MDT). Measuring the value of these services is challenging but is important for quality improvement and commissioning. This retrospective analysis of the activity of an inner city community respiratory service documents the nature of the caseload, interventions made and their impact on usual care provision. Method: The CORE-MDT, accepting referrals from GPs and three acute hospital trusts, is based at three localities and includes respiratory nurses, physiotherapists, quit-smoking advisors, clinical psychologists and respiratory consultant support. Care is delivered at home with hospital in-reach during every admission. A bespoke iPad App database (HandBase) was designed for information documentation and sharing from case management and consultant-led MDT discussion of patients. A retrospective analysis of records was made of sequential referrals from Sept 2014 to March 2015. Demographics, disease severity, comorbidities, social deprivation, duration of management, nature of intervention and healthcare resource utilisation over 6/12 were documented. Hospital data allowed estimation of bed-day savings based on average length of stay for acute exacerbations of COPD (AECOPD). Results: Records from 83 patients (most with COPD) were reviewed. Mean [SD] FEV1: 0.98 [0.38]L. Patients had multiple comorbidities, high smoking prevalence, deprivation and isolation (Table 1 ). Mean[SD] duration of CORE team management: 5.2[4.9]months. ~50% of patients were then discharged to usual care. 17/34 (50%) completed pulmonary rehabilitation, 11 saw a psychologist and 6/12 (50%) achieved smoking cessation. Mortality was 6%. Hospital bed-days usage (p = 0.001) and GP visits (p = 0.02) were reduced during active case management compared to the year before referral. Domiciliary management of 105 AECOPD reduced GP workload with an estimated £58 000 savings in admission avoidance for (n = 30) patients with baseline hypoxia <92% or >2 admissions in the year prior to CORE management HRG DZ-21K: £2000/admission). Conclusions: The service has improved quality of care for these complex sick patients and generated significant savings in GP workload and admission avoidance which should underpin service commissioning and provision. The use of Handbase has facilitated consistency in evidence-based care and record-keeping, information sharing and evaluation of CORE-MDT activity.